FORMATION OF COGNITIVE INDEPENDENCE OF STUDENTS OF ECONOMIC DIRECTION OF TRAINING IN THE PROCESS OF STUDYING PROFESSIONAL DISCIPLINES - S.V. Malykhina (Academy of Cognitive and Natural Sciences, 2022)
The article deals with some actual problems concerning the formation o f students' (are being trained to be economists) cognitive self directed activities in the process o f special disciplines studies.